2018
DOI: 10.1002/sdtp.12576
|View full text |Cite
|
Sign up to set email alerts
|

29‐3: Highly Versatile and Stable Photoalignment Process for AMLCDs

Abstract: A simple process for a reactive mesogen (RM) alignment layer is demonstrated with potential wide spread application in liquid crystal devices. A low concentration (0.3% wt) of RM dissolved in a liquid crystal is aligned by an azodye layer.After polymerization of the RM, the azodye is "bleached" to remove its visible absorption. The result is a versatile, low cost, stable alignment layer that is practical for AMLCDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…We conclude that for thin LC films, the anchoring strength is sufficient even with very thin photoalignment layers. Concentrations as low as 0.1% in DMF have been shown to work well for photoalignment [28]. Hence, the concentration of BY can be selected depending on the target application.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that for thin LC films, the anchoring strength is sufficient even with very thin photoalignment layers. Concentrations as low as 0.1% in DMF have been shown to work well for photoalignment [28]. Hence, the concentration of BY can be selected depending on the target application.…”
Section: Discussionmentioning
confidence: 99%
“…Life tests re-expose the LC-filled cells to linearly polarized blue light at 45° with respect to the original photo-alignment process. Photo-bleaching re-exposes the cells with un-polarized blue light to eliminate the photosensitivity of the azo dye layer [ 10 , 11 ] because the brilliant yellow molecules re-orient along the un-polarized light propagation direction where no light absorption occurs and the molecules are at rest. If the monomer was not polymerized on (or close to) the surface, the resulting cells would show: (1) re-alignment with life test and/or photo-bleaching, (2) some light scattering observation because of the network through bulk, or (3) increased threshold voltage as indicated by the T/V curve after UV polymerization.…”
Section: Methodsmentioning
confidence: 99%
“…To simplify the process, V. Finnemeyer et al [ 6 ] proposed that a small amount of reactive monomer added to the liquid crystal host could provide excellent stabilization of the alignment by phase separation. Additionally, C. McGinty et al [ 10 , 11 ] showed that the underlying azodye layer can be photo-bleached to eliminate its visible absorption as well as its ability to re-orient further.…”
Section: Introductionmentioning
confidence: 99%